2022
DOI: 10.1186/s12966-022-01326-9
|View full text |Cite
|
Sign up to set email alerts
|

The association between the built environment and intervention-facilitated physical activity: a narrative systematic review

Abstract: Background A diverse range of interventions increase physical activity (PA) but few studies have explored the contextual factors that may be associated with intervention effectiveness. The built environment (BE) may enhance or reduce the effectiveness of PA interventions, especially interventions that encourage PA in neighbourhood settings. Several studies have investigated the effects of the neighbourhood BE on intervention-facilitated PA, however, a comprehensive review of evidence has yet to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 79 publications
1
11
2
Order By: Relevance
“…We hypothesized that changes in self-reported physical activity at 4 weeks and 12 weeks during the intervention would be significantly higher for adults residing in neighborhoods that were more versus less walkable. Adding to the mixed evidence [ 32 ] and contrary to our hypothesis, we found that level of neighborhood walkability did not affect changes in physical activity and sedentary behavior resulting from participation in an individual-level physical activity intervention. Congruent with previous studies [ 3 , 5 , 6 ] we did, however, find increases in physical activity as a result of participating in a short-term internet-delivered pedometer-facilitated intervention, independent of neighborhood walkability.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…We hypothesized that changes in self-reported physical activity at 4 weeks and 12 weeks during the intervention would be significantly higher for adults residing in neighborhoods that were more versus less walkable. Adding to the mixed evidence [ 32 ] and contrary to our hypothesis, we found that level of neighborhood walkability did not affect changes in physical activity and sedentary behavior resulting from participation in an individual-level physical activity intervention. Congruent with previous studies [ 3 , 5 , 6 ] we did, however, find increases in physical activity as a result of participating in a short-term internet-delivered pedometer-facilitated intervention, independent of neighborhood walkability.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite the null findings, to our knowledge this is the first study to estimate the effect of an interaction between objectively-measured walkability and a physical activity intervention on context (i.e., neighborhood) specific physical activity [ 32 ]. Our study has several positive attributes such as measuring change in a range of context-specific physical activities over three time points, statistical adjustment for baseline motivational characteristics (intention, self-efficacy), perceived walkability, preference for residing in a walkable neighborhood, self-rated health, and sociodemographic characteristics, using an established walkability index (Walk Score®), and recruitment of adults who were in the contemplation and preparation stages of physical activity change.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations